2020
DOI: 10.3390/v12010062
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and Genetic Diversity of Rotaviruses among under-Five Children in Ethiopia: A Systematic Review and Meta-Analysis

Abstract: Rotavirus infection is the major cause of acute gastroenteritis among children globally. Sub-Saharan Africa including Ethiopia is disproportionally affected by the disease. The aims of this review were to determine the pooled prevalence of rotavirus infection among children under-five and to identify the dominant rotavirus genotypes in Ethiopia. Twelve studies were included to estimate the pooled prevalence of rotavirus acute gastroenteritis and five studies were used to determine predominantly circulating gen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

12
21
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 27 publications
(90 reference statements)
12
21
0
Order By: Relevance
“…S. flexneri (20%), and Salmonella Typhi (1.9%) have been reported elsewhere [ 10 ]. The proportion of rotavirus infection detected (25%) was virtually identical to the findings of a recent analysis focussing on prevalence of rotavirus infection in children under-five in Ethiopia [ 42 ]. The occurrence of rotavirus infections in children aged under 3 years indicates the need to target this age group with rotavirus/adenovirus screening via RDT, to minimize antimicrobial over-prescription.…”
Section: Discussionsupporting
confidence: 79%
“…S. flexneri (20%), and Salmonella Typhi (1.9%) have been reported elsewhere [ 10 ]. The proportion of rotavirus infection detected (25%) was virtually identical to the findings of a recent analysis focussing on prevalence of rotavirus infection in children under-five in Ethiopia [ 42 ]. The occurrence of rotavirus infections in children aged under 3 years indicates the need to target this age group with rotavirus/adenovirus screening via RDT, to minimize antimicrobial over-prescription.…”
Section: Discussionsupporting
confidence: 79%
“…For example, rotavirus vaccines were introduced in the six countries included in this study between 2012 and 2014 and the G12 strains analysed in this study were collected between 2010 and 2014. To substantiate further, various studies from Ethiopia have reported G12 rotaviruses as a dominant strain both pre- and post-vaccine introduction [ 65 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, rotavirus vaccines were introduced in the six countries included in this study between 2012-2014 and the G12 strains analysed in this study were collected between 2010-2014. To substantiate further, various studies from Ethiopia have reported G12 rotaviruses as a dominant strain both pre-and post-vaccine introduction [65].…”
Section: Evidence Of Genetic Variation Was Observed Amongst the Four mentioning
confidence: 98%